2011
DOI: 10.1002/pri.477
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the Physiological Cost Index among Individuals with a Lower‐Limb Amputation and Healthy Adults

Abstract: The within-day test-retest reproducibility of the PCI was excellent among individuals with lower-limb amputations and healthy adults in terms of intra-class correlation and acceptable in terms of agreement. The SDC, which was calculated for each group, should be considered when demonstrating an individual difference after an intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
2
20
0
2
Order By: Relevance
“…The mean 6MWT distance was half of the estimated normative values [18, 28], which was similar to the results found in another study at a later stage after stroke [29]. The energy cost measured using the PCI was approximately double compared to healthy people [19, 20, 30] and comparable to another study of the energy costs involved in over-ground walking in stroke subjects [21]. However, both the heart rate and the ratings of perceived exertion indicated that the walking tests in the current study were not very strenuous, probably because of the low velocity.…”
Section: Discussionsupporting
confidence: 82%
“…The mean 6MWT distance was half of the estimated normative values [18, 28], which was similar to the results found in another study at a later stage after stroke [29]. The energy cost measured using the PCI was approximately double compared to healthy people [19, 20, 30] and comparable to another study of the energy costs involved in over-ground walking in stroke subjects [21]. However, both the heart rate and the ratings of perceived exertion indicated that the walking tests in the current study were not very strenuous, probably because of the low velocity.…”
Section: Discussionsupporting
confidence: 82%
“…The PCI protocol has shown acceptable reliability among individuals with lower-limb amputation. 26 Although not part of the OPRA study protocol, a description of the prosthesis at each time point was included in the current study. This was recorded by a certified prosthetist and is described in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The PCI was calculated as the difference between walking and resting heart rate divided by the distance (meters) walked. This score has high test-retest reproducibility among individuals with lower-limb amputations and healthy adults, and acceptable intraclass correlation [13]. In a study by Fredrickson et al [9], comparing healthy adults and stroke victims, the PCI was validated as an appropriate proxy for the oxygen cost of walking with a correlation coefficient to oxygen consumption of r = 0.83; the correlation coefficient of the PCI to walking speed was reported as r = À0.461.…”
Section: Methodsmentioning
confidence: 99%